Characterisation of Novel Self-Healing Composites Using Acousto-Ultrasonic Testing - Claudia Barile; Vimalathithan Paramsamy Kannan; Giulia Derosa; Giovanni Pappalettera (Engineering Proceedings)
Self-healing composites are designed based on natural healing processes such as bone regeneration and blood coagulation. These composites have polymeric material containing covalent adaptable networks that rearrange their molecular structure when heated, thereby serving as a healing agent. The inclusion of the healing polymers into the principal matrix of the fiber-reinforced composites alters their off-axis properties. In addition, the healing agents tend to bleed out of the composite structures upon heating. It is, therefore, essential to characterize the extent of the changes in the off-axis properties of the self-healing composites. In this research work, three different configurations of self-healing composites are subjected to three-point bending tests, and their healing characteristics are studied using Acousto-Ultrasonic tests. Frequencies of the propagating stress waves in the AU tests are used to analyze the different conditions of the self-healing composites, such as virgin, damaged, damaged-partially healed, and damaged-fully healed. The results show that the AU test could potentially be used to evaluate the healing behavior of these fiber-reinforced self-healable composites.